Robust singlet fission in pentacene thin films with tuned charge transfer interactions - Broch, K.; Dieterle, J.; Branchi, F.; Hestand, N. J.; Olivier, Y.; Tamura, H.; Cruz, C.; Nichols, V. M.; Hinderhofer, A.; Beljonne, D.; Spano, F. C.; Cerullo, G.; et al. (Nature communications, 2018)
Singlet fission, the spin-allowed photophysical process converting an excited singlet state into two triplet states, has attracted significant attention for device applications. Research so far has focused mainly on the understanding of singlet fission in pure materials, yet blends offer the promise of a controlled tuning of intermolecular interactions, impacting singlet fission efficiencies. Here we report a study of singlet fission in mixtures of pentacene with weakly interacting spacer molecules. Comparison of experimentally determined stationary optical properties and theoretical calculations indicates a reduction of charge-transfer interactions between pentacene molecules with increasing spacer molecule fraction. Theory predicts that the reduced interactions slow down singlet fission in these blends, but surprisingly we find that singlet fission occurs on a timescale comparable to that in pure crystalline pentacene. We explain the observed robustness of singlet fission in such mixed films by a mechanism of exciton diffusion to hot spots with closer intermolecular spacings. Singlet fission is desirable for highly efficient solar cells, yet the details of the process remain elusive. Here, Broch et al. show that the changes in bulk intermolecular interactions can have little effect on the singlet fission rate in a mixture of pentacene and weakly interacting spacer molecules.